2010
DOI: 10.1111/j.1439-0396.2010.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macroalgae enriched with microelements on egg quality parameters and mineral content of eggs, eggshell, blood, feathers and droppings

Abstract: This study presents results obtained from feeding experiment on laying hens, which were fed with the diet supplemented with two marine macroalgae: Enteromorpha prolifera and Cladophora sp., enriched with microelements [Cu(II), Zn(II), Co(II), Mn(II), Cr(III)]. The applicability of the preparation was tested on five experimental groups of laying hens and one control group. In the control group, microelements were supplemented in the inorganic form, whereas in experimental groups, Cu, Zn, Co, Mn and Cr were repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
(33 reference statements)
3
58
0
3
Order By: Relevance
“…It was also noticed that the presence of green macroalgae Enteromorpha prolifera and Cladophora sp. in laying hens' diet influenced advantageously egg weight, eggshell thickness, as well as the body weight of hens [19]. Also Witkowska et al (2014a) showed that the qualities of eggshell strength, eggshell thickness, albumen height and yolk color of the hens fed with soybean enriched via biosorption were enhanced.…”
Section: Introductionmentioning
confidence: 89%
“…It was also noticed that the presence of green macroalgae Enteromorpha prolifera and Cladophora sp. in laying hens' diet influenced advantageously egg weight, eggshell thickness, as well as the body weight of hens [19]. Also Witkowska et al (2014a) showed that the qualities of eggshell strength, eggshell thickness, albumen height and yolk color of the hens fed with soybean enriched via biosorption were enhanced.…”
Section: Introductionmentioning
confidence: 89%
“…erefore, in the feed industry and among breeders, there is an increasing interest in the possibility of using new materials such as algae enriched in microcomponents [11], fossil materials [12], food industry waste such as yeast [13], and other organic waste [5]. e appropriate content of macro-and microelements in compound feed is also necessary from the point of view of production economics because it will not only allow obtaining products with an increased content of these ingredients but also help to maintain the health and production parameters of animals at an optimal level [14].…”
Section: Enrichment Of Eggs Withmentioning
confidence: 99%
“…In our previous studies we showed that biomass enriched with microelement ions constituted a source of highly bioavailable minerals to animals (laying hens, pigs, goats) and can partly replace traditionally used inorganic salts as a main source of microelements [20][21][22]. In these studies it was shown that the bioavailability of microelements from the enriched biomass was higher than from inorganic salts.…”
Section: Introductionmentioning
confidence: 98%
“…Before the analysis, enriched biomass (about 0.5 g) was digested with 5 mL of concentrated 69% nitric acid (Supra pure grade from Merck, Darmstadt, Germany) in Teflon bombs in a microwave oven (type Milestone MLS-1200 MEGA, Bergamo, Italy). The solution after mineralization was diluted to 50 mL and analysed by ICP-OES [20,31].…”
Section: Inductively Coupled Plasma-optical Emission Spectrometrymentioning
confidence: 99%